Effect of electron mobility variation on short channel effects in nanoscale double gate FinFETs: A comparative study - Shehu, Nura Muhammad; Garba Babaji; Mutari Hajara Ali (International Journal of Physical Research, 2024)
This work investigates the impact of electron mobility variations on short channel effects (SCEs) in different semiconductor materials using FinFETs. Using PADRE simulator, the work examines Gallium Arsenide (GaAs), Gallium Antimonide (GaSb), Gallium Nitride (GaN), and Silicon (Si) FinFETs, analyzing performance metrics such as Drain Induced Barrier Lowering (DIBL), Subthreshold Swing (SS) and Threshold Voltage roll-off. The result shows that GaN-FinFET exhibits lowest subthreshold swing of 63 mV/dec at electron mobility of 10000 cm2/Vs, and threshold voltage of 0.44V at electron mobility of 10000 cm2/Vs, while Si-FinFET exhibits lowest DIBL of 3 mV/V at (4000-10000) cm2/Vs. This finding contributes to advancing the understanding of short channel effects in nanoscale FinFETs and provides valuable insights for optimizing device performance in future semiconductor technologies.
Keywords: DIBL; Electron Mobility; FinFETs, SCEs, GaAs, GaSb.